Anti-cancer effects of frankincense methanolic extract on brain metastatic breast cancer cells - Mohammad Kamalabadi-Farahani; Fatemeh Jamshidi Adegani; Roqaye Karimi; Amir Atashi (Avicenna Journal of Phytomedicine)
Objective: Brain metastasis in patients with breast cancer is considered a deadly event. The oleogum resins of Boswellia species, known as Frankincense  has been found to have anti-cancer properties in many studies. The main purpose of our research was to evaluate these effects on brain metastatic cancer cells.Materials and Methods: Primary (4T1T) and brain metastatic (4T1B) tumor cells were isolated from breast cancerous mice. Cytotoxic, apoptotic, and anti-metastatic effects of the methanolic extract of frankincense were evaluated with MTT assay, propidium iodide (PI) flow cytometric assay, and scratch test, respectively. Zymography assay was used to evaluate the effects of extract on the matrix metalloproteinases-2 and -9 (MMP-2 /9) expression/activity.Results: The methanolic extract of frankincense has significant cytotoxic and apoptotic effects on 4T1B cells (p<0.001). Interestingly, 4T1B cells are more prone to these effects than 4T1T cells. In 4T1B, the anti-metastatic effects of frankincense extract were confirmed. Frankincense suppressed MMP-2/9 protein expression both in 4T1T and 4T1B.Conclusion: Our findings indicated that frankincense extract has a potent cytotoxic effect on brain metastatic tumor cells and induces apoptosis in these cells. Unlike many anti-cancer drugs which have very little ability to combat and kill brain metastatic cancer cells, frankincense extract can be considered a suitable candidate to fight these cells.